ANALISIS PENDIDIKAN KARAKTER PEDULI SOSIAL DALAM PEMBELAJARAN IPAS MATERI “DISINI TEMPAT TINGGALKU” KELAS IV SD NEGERI NGEMPLAK SURAKARTA TAHUN AJARAN 2024/2025 - Zintya Intan Aini; Anita Trisiana; Oktiana Handini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Character education plays an important role in shaping a generation that is not only intellectually smart but also empathetic and caring toward others. One of the core values that should be instilled early on is social care. This study aims to describe the implementation strategies, behavioral indicators, and forms of value integration of social care character education in IPAS learning on the topic “This Is My Place of Residence” in Grade IV of SD Negeri Ngemplak Surakarta for the 2024/2025 academic year. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation. Data validity was ensured through source and technique triangulation. The results show that the implementation of social care values is carried out through routine activities such as greetings and donations, spontaneous actions like giving praise or reprimands, teacher role modeling, and a school environment that fosters caring behavior. Indicators of students’ social care are reflected in their habits of sharing food, helping peers, and respecting school staff. Social care values are integrated into IPAS learning using a contextual approach that links the content to students' surrounding environment. In conclusion, the implementation strategies of social care character education are quite effective in fostering students’ caring attitudes, and IPAS learning serves as a relevant and contextual medium to internalize these values.